Editorial (OverHolland, 2018)
We open this edition of OverHolland with the very sad news that one of the journal’s editors, Henk Hoeks, died on 29 January 2017. Born on 14 March 1947, Henk was one of the founders of the publishing house SUN (Socialistische Uitgeverij Nijmegen, ‘Nijmegen Socialist Publishers’), where he worked as an editor from 1970 to 2008. From the outset, as he himself said, SUN rested on two main pillars: philosophy and history, to which architecture was added as a third pillar in the course of the 1970s. The new focus on architecture was boosted by SUN’s long-established links with rebellious students at Delft University of Technology’s faculty of architecture.Under Henk Hoeks’s editorship, based on his contacts and friendships from that time, a magnificent series of books on architecture was published; after SUN Architecture was wound up in 2011, he arranged for these to be published henceforth by Vantilt. Henk Hoeks was widely praised for his carefully crafted publications and his remarkable ability to bring out writers’ talents – with particular success in the field of architecture. From 1990 to 2003 he ran the Dutch architectural journal OASE (issues 28-61), founded by architecture students at Delft. It was a breeding ground for young talent. Since 2004 part of this role has been taken over by the OverHolland, architectonische studies voor de Hollandse stad (‘About Holland: architectural studies on Holland’s towns and cities’) series. Henk Hoeks was especially interested in architectural theory and history. He expressed his motives for this, perhaps more clearly than anyone else, in the following words: ‘Given his philosophical outlook, he was above all fascinated by form. Form restricts and individualizes – it is the intelli-gible aspect of things. Form makes things identifiable, and demarcates functions, for example in an urban structure’, he wrote of himself in the third person in the 2008 booklet Goed vastzittende spijkers (‘Well-hammered nails’). He recalled the eye-opening illustrations on a Piranesi altar, and Manfredo Tafuri’s commentary on them in Architecture and utopia: ‘He experienced the illustrations, and the author’s explanatory text, as a shock and a liberation. Gian Battista Piranesi’s altar taught him a lesson he was very keen to learn, and would never forget. It told him about the double face of culture: a sensual, colourful, multifaceted, elegant front side that conceals a bare rear side made up of purely abstract geometric forms, with the naked globe as its most striking feature. There is no basis here in nature or spon-taneity, for anyone that looks closely will discover that the complex structure of the front is made up of features from long-vanished cultures, such as the three stacked-up sarcophagi. Culture is an interplay with historical fragments, a set of which we appropriate and, in so doing, turn into an amalgam of heterogeneous elements. We live in a culture of “constructors”; the abundance of images and the sensual wealth conceal a fundamental “poverty”, that of the calculating intellect. The last word is with the mute globe, emptiness and silence. And yet St Basil, in mid-flight to heaven, is lit from above – a symbol of telos, salvation?’ Despite his radical views, Henk Hoeks never entirely abandoned comforting ideas – saving him, and us, from much chagrin and fanaticism. More cheering news is that the previous issues of OverHolland are now available online at http:// journals.library.tudelft.nl/index.php/overholland and can be consulted with the help of an index. OverHolland 18/19 has now added a new search term. The theme of this issue is ‘the university and the city’. A number of articles look closely at the foundation and development of the Delft and Eindhoven Universities of Technology. The comparison between the two mainly focuses on how these urban institutions influenced the two cities’ spatial development. Particular attention is paid to a far-reaching change in the historical development of university buildings: the introduction of laboratories for purposes of research. The change in the university/city relationship that took place because of the increased size of the buildings and the greater resulting inconvenience is clearly visible in the development of both institutions. Delft and Eindhoven were the first two post-war Dutch universities to introduce the ‘campus’ model: the university as a separate district of the city. The degree of the university’s spatial independence has been a recurring theme in the debate about its accommodation. The separate identity of the university has continued to clash with the need to integrate it into the city so that it can continue to function as an urban institution. The studies carried out for this issue of OverHolland are part of a joint project by researchers at the Delft and Eindhoven faculties of architecture, supervised by Esther Grams-bergen and Bernard Colenbrander. The project was funded by the two universities’ housing and property departments. The core of the research is the cartographical section, which uses techniques developed earlier in Delft’s research into the spatial development of towns and cities in the Randstad conurbation, discussed in previous issues of OverHolland. The spatial development of the two cities and the accommodation of the two universities and associated institutions is mapped out in successive stages. What is new is the way in which changes in the spatial pattern of the two campuses is documented in detailed ground plans and cross-sections. This mainly concerns the arrangement of the unbuilt ground level in relation to the plinths of the buildings. At the same time, typological study of the buildings on both campuses makes clear how the distribution and nature of indoor spaces are related to the purpose and arrangement of the surrounding outdoor spaces. The conversion of this kind of analysis into ‘rules for rebuilding’ that can serve as guidelines to the transformation of the campus is the particular expertise of Bauhütte, the ‘design-based research group’ supervised by Christian Rapp. The group was set up to produce a master plan for the further transformation of the Eindhoven campus and its supervision. The plan shows how the need for new kinds of university buildings can be combined with a campus that is now part of the architectural heritage. Bauhütte also drew up the master plan for the transformation of the Tilburg University campus. As part of this, KAAN Architecten has designed a new Teaching and Self-Study Centre, which is now under construction. Details are provided in the article by Kees Kaan. Finally, the Polemics section of OverHolland commemorates the fact that Aldo Rossi’s book The architecture of the city was published fifty years ago. To mark the occasion, Ezio Bonfanti’s October 1970 article Elementi e costruzione: note sull’architettura di Aldo Rossi from the journal Controspazio – the first architectural-theory analysis of Aldo Rossi’s designs – is published here for the first time in Dutch and English translations, together with Rossi’s notes and the letter he wrote to Bonfanti about them, as well as Bonfanti’s reply. An introduction to these unique documents is provided by Stefano Milani.